Some thoughts around developing missional South African congregations based upon the church rediscovering its identity in the grace of God - Tucker, Roger (Stellenbosch Theological Journal, 2016)
The UPCSA have established the development of missional congregations as the overarching goal of the denomination. The UPCSA is a reformed church and as such attaches great importance to theology, especially that which originates in the character and nature of God. It is therefore suggested that a contextual practical theology based upon the perfection of the grace of God may enable missional congregations to be developed, as they rediscover their identity in that grace. This then will be the basis for building congregations that are truly missional at heart and not just superficially so. The study will be contextualized to the South African scene and applied to local congregations in order to try to help them rediscover their true identify in Christ, and to provide a basis for understanding “missional” and thus what transformation may entail.